Graft Preparation with Intraoperative Vancomycin Decreases Infection after Anterior Cruciate Ligament Reconstruction: A Review of 1640 Cases. Issue 7 (31st July 2020) - Shamrock, Alan; Cates, William; Cates, Robert; an, qiang; Wolf, Brian; Bollier, Matthew; Duchman, Kyle; Westermann, Jacqueline Baron Robert
Objectives: Septic arthritis is a rare but devastating complication following anterior cruciate ligament (ACL) reconstruction. Reported infection rates following ACL reconstruction are low, but associated with high morbidity including reoperation and inferior clinical outcomes. The purpose of the current study was to investigate the rate of infection after ACL reconstruction with and without graft preparation with vancomycin irrigant. Methods: All ACL reconstructions performed from May 2009-August 2018 at a single, large academic institution were reviewed and categorized based on vancomycin use. Those with <90-day follow-up, intraoperative graft preparation with an antibiotic other than vancomycin, or previous ipsilateral knee infection were excluded. Infection was defined as a return to the operating room for irrigation and debridement within 90 days of ACL reconstruction. Descriptive and inferential statistical analysis using t-tests and Poisson regression were performed, with statistical significance defined as p<0.05. Results: In total, 1, 640 patients (952 males; 58.0%) with a mean age of 27.7 + 11.4 years underwent ACL reconstruction (1, 379 primary procedures; 84.1%) and were included for analysis. Intraoperative vancomycin was used in 798 cases (48.7%) while 842 ACL reconstructions (51.3%) were performed without intraoperative vancomycin. There were eleven total infections (0.7%), with ten infections occurring in patients without vancomycin-soaked grafts (1.2%) and one infection occurring in grafts soaked in vancomycin (0.1%; p=0.008). Age (p=0.571), gender (p=0.707), smoking (p=0.407), surgeon (p=0.124), and insurance type (p=0.616) were not associated with postoperative infection. There was an 89.5% relative risk reduction with the use of intraoperative vancomycin. Increased body mass index (BMI) (p=0.029), increased operative time (p=0.001), and absence of ACL graft preparation with vancomycin (p=0.032) independently predicted postoperative infection. Conclusion: The use of vancomycin-soaked grafts was associated with a ten-fold reduction in postoperative infection after ACL reconstruction (0.1% versus 1.2%; p=0.032). Other risk factors for postoperative infection after ACL reconstruction included increased BMI and increased operative time. Table 1. Operative variables of the study groups. *=statistical significance (+) Vancomycin n=798 (48.7%) (-) Vancomycin n=842 (51.3%) p-value Operative Time (minutes) 98.6± 42.3 130.5± 54.3 *<0.001 Autograft 580 (72.7%) 536 (63.5%) *<0.001 Allograft 210 (26.3%) 237 (28.2%) 0.436 Hybrid Autograft/Allograft 8 (1.0%) 70 (8.30%) *<0.001 Revision ACL 128 (16.0%) 133 (15.8%) 0.901 Multi-ligament 90 (11.3%) 61 (7.2%) *0.005 Perioperative Cefazolin 716 (89.7%) 747 (88.6%) 0.511 Table 2. Demographic and operative variables of patients with and without infection. BMI=body mass index; IRR=incidence rate ratio; CI= confidence interval; *=statistical significance (+) Infection n=11 (0.7%) (-) Infection n=1627 (99.3%) IRR (95% CI) p-value Age (years) 30.0± 14.0 27.7± 11.3 - 0.571 Male 7 (63.6%) 945 (58.0%) 1.266 (0.371-4.342) 0.707 BMI (kg/ m 2 ) 33.9± 10.0 27.5± 6.2 - *0.029 BMI>30 7 (63.6%) 438 (26.9%) 4.699 (1.376-16.050) *0.014 Diabetes 0 (0%) 25 (1.5%) - 1.000 Smoking 3 (27.4%) 286 (17.6%) 1.753 (0.465-6.608) 0.407 Private Insurance 11 (100%) 1466 (90.0%) - 0.616 Caucasian Race 8 (72.7%) 1337 (82.1%) 2.076 (0.551-7.824) 0.281 Operative Time (minutes) 125.6± 48.5 114.9± 51.4 - *0.001 Tourniquet Use 9 (81.8%) 1378 (84.6%) 1.334 (0.666-15.942) 0.800 Postoperative Aspirin 10 (90.9%) 1450 (89.0%) 4.211 (0.836-9.474) 0.841 Vancomycin 1 (9.1%) 797 (48.9%) 0.106 (0.014-0.824) *0.032 Autograft 4 (36.4%) 1112 (68.3%) 0.289 (0.079-0.919) *0.045 Hamstring Autograft 3 (27.3%) 761 (46.7%) 0.431 (0.114-1.623) 0.213 Quadriceps Autograft 1 (9.1%) 35 (2.2%) 4.456 (0.570-34.806) 0.154 Hybrid Autograft/Allograft 1 (9.1%) 77 (0.6%) 2.003 (0.256-15.644) 0.508 Table 3. Multivariate analysis results with incidence rate ratios (IRR) and 95% confidence intervals (CI). Multiple models were created to evaluate the effect of vancomycin ACL graft preparation on postoperative infection controlling for a single variable to prevent overfitting. Vancomycin use remained associated with decreased postoperative infection in each model. *=statistical significance Variable Controlled For IRR (95% CI) p-value Revision 0.117 (0.015-0.923) *0.042 Other ligamentous procedure 0.010 (0.013-0.782) *0.028 BMI 0.109 (0.014-0.856) *0.035 Operative Time 0.179 (0.021-0.450) *0.011 Autograft 0.119 (0.015-0.931) *0.042 Hybrid 0.107 (0.014-0.843) *0.034 Table 4. Infection rates, total cases, and cases with vancomycin prepared grafts by treating surgeon. Infections Total Cases Vancomycin Cases (%) Infection Rate Surgeon 1 3 198 4 (2.0%) 1.5% Surgeon 2 4 243 2 (0.8%) 1.7% Surgeon 3 1 552 435 (78.8%) 0.2% Surgeon 4 0 125 1 (0.8%) 0% Surgeon 5 0 30 29 (96.7%) 0% Surgeon 6 3 492 327 (66.5%) 0.6%